Creating Evidence for Better Health Financing Decisions : A Strategic Guide for the Institutionalization of National Health Accounts - Maeda, Akiko (Washington, DC: World Bank, 2013)
One of the key constraints to improving health outcomes in the developing world relates to equitable and efficient health financing. In most developing countries, a large portion of health expenditure is private and out-of-pocket (Gottret and Schieber 2006). This book represents a synthesis of lessons learned from country experiences and is intended to serve as a strategic guide to countries as they design and implement their policy to develop nationally relevant and internationally comparable data, collected in a routine and cost-effective manner. National Health Accounts (NHA) substantially contribute to the effort of improving health financing policy at global and country levels and offer a globally recognized framework for collecting, compiling, and analyzing data on health expenditures to and within the health system. As part of this effort, a framework has emerged that presents NHA activities as a cycle of activities with a clear purpose to serve policy makers, extending beyond the production of data: it involves the broad dissemination of that data and their translation into insightful analysis that can form an evidence base for effective policy making, underpinned by the nature of a given country's governance structure, human resources, and financing abilities. This book makes a distinct contribution in the way it addresses each step in the cycle of activities, assisting countries take greater ownership of the process of producing evidence and to make greater use of that evidence for better health financing decisions.